PENGARUH KEBIASAAN DOA BERSAMA DALAM KELUARGA KRISTIANI BAGI PERKEMBANGAN IMAN ANAK - Mrs Lusia; Agustinus Supriyadi (Bahasa Indonesia, 2019)
The family has a great responsibility and role in the child's faith education. Children's faith education can be done through a family’s together prayer habit. One of the ways commonly used as a habit for Christian families in educating and nurturing children's faith is to instill the habit of praying in the family. Does the Christian family have a good understanding habit of the praying together in the Christian Family? Does the family have an awareness of the faith education for the development of the child’s faith? Do they understand the effect of praying together in their family for the development of the child’s faith? Based on these issues the research in this paper attempts to analyze how far the influence of family prayer for the development of the child’s faith.This study uses a qualitative method. The respondents of this study are Christian families who have children in the age range 0 to 12 years, and who live in the IV region of St. Cornelius Madiun Parish. The number of respondents in this study were 8 families. Based on the results of the study, all respondents or 8 respondents (100%) realized that the together praying in the family has a great influence on the development of the child's faith. There were 7 respondents (58,33%) emphasize that habit of the praying together in the Christian family can give spiritual provisions for the children, besides 5 respondents (62.5%) who said that habit of the praying in the Christian family is a means to educate children and 4 respondent (36,36%) expressed the habit of praying together in the family can fostering attention in the family.